DELIVERY. OF ARTHROGRYPOSIS-SCOLIOSIS FETUS IN A BUFFALO THROUGH PARTIAL FETOTOMY - GHUMAN, S P S; NAZIR, G; GANIE, M A; PHAWA, B (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to arthrogryposis-scoliosis fetus in a Murrah buffalo and its vaginal delivery is reported.
Keywords: Arthrogryposis-Scoliosis fetus; Fetotomy; Vaginal delivery; Buffalo